Promoting adolescent girls' active school travel in Ghana: Contextualizing health belief model and theory of planned behavior - Stephen Agyeman; Philip Kofi Alimo (Journal of Cycling and Micromobility Research)
In recent years, efforts to promote safer active school travel (AST), i.e., walking and cycling behaviors in girls, have heightened in light of huge gender disparities in micromobility adoption. In developing countries where transport infrastructure is not advanced, and AST adoption is influenced by societal perceptions, theorizing empirical studies will help better explore and understand the travel needs of girls for effective planning. This study investigated the factors influencing AST behaviors of 232 adolescent girls in primary, junior, and senior high schools based in Sunyani Municipality, Ghana. A novel combination of the Health Belief Model and the Theory of Planned Behavior was employed to formulate a conceptual model that was evaluated using SEM-MIMIC modeling. Results revealed that age plays a significant role in AST preferences, with younger girls favoring walking and older girls showing interest in cycling. Interventions can capitalize on this to promote cycling habits during the transition to senior high school. Moreover, environmental attitudes have the most decisive influence on the perceived social benefits of AST, while perceived parental support positively impacts safety self-efficacy. Together with perceived parental support, safety self-efficacy, and distance/accessibility barriers, they significantly influence girls' intentions to use active transportation. Authorities can adopt proposed targeted interventions such as the walking school bus and bicycle train concepts to make AST more attractive to girls.